Shaping specialist treatment of Stevens–Johnson syndrome/toxic epidermal necrolysis. (19th November 2019) - Walsh, S.; Creamer, D.
Abstract : Linked Article : Chaby et al. Br J Dermatol 2020; 182: 618–624 .